The RAF and tribal control : airpower and irregular warfare between the World Wars - Newton, Richard D. (University Press of Kansas, 2019)
"Modern air power analysts have tended to hold the British air control experience in the Middle East between the two World Wars as the exemplar of how technology might solve the civil-military challenges of small wars. By seeking to find repeatable, technologically-oriented solutions to what are inherently human problems, these analysts have missed the Royal Air Force's innovative approach to air power and what made it possible to substitute air power for battalions of soldiers in certain situations. The RAF made air power personal by placing airmen who understood the local cultures in and among the populace. They served as the conduit for information, communication, and insight between the colonial administration and the tribes and villages. This book, then, brings to light the contributions of those embedded airmen, the Special Service Officers, who made possible the integration of air power into the civil administration of the colonies and Mandates"--